Novel Ag3PO4/boron-carbon-nitrogen photocatalyst for highly efficient degradation of organic pollutants under visible-light irradiation. (15th August 2021) - Wang, Shuo; Zhang, Wei; Jia, Fuchao; Fu, Hongling; Liu, Tingting; Zhang, Xuan; Liu, Bo; Núñez-Delgado, Avelino; Han, Ning
Abstract: Ag3 PO4 is an indirect bandgap semiconductor with excellent photocatalytic activity. However, it has not been widely used so far for the treatment of polluted wastewaters. This scarce use in wastewater treatment can be mainly attributed to its large crystallite size, which would be due to rapid agglomeration during the synthesis process, as well as to the photo-corrosion problem affecting this material. Hence, it would be crucial to develop a photocatalytic system involving Ag3 PO4 nanoparticles with enhanced properties, such as higher specific surface area and excellent photocatalytic stability. To meet this demand, a novel Ag3 PO4 /boron carbon nitrogen (Ag3 PO4 /BCN) composite photocatalyst was successfully prepared in the present study via electrostatically driven self-assembly and ion exchange processes. After characterization and assessment, it was shown that the as-prepared Ag3 PO4 /BCN nanocomposite photocatalyst not only contains smaller Ag3 PO4 nanoparticles, but also exhibits an enhanced visible-light photocatalytic activity for Rhodamine B (RhB) Methyl Orange (MO) and Tetracycline (TC) and improved stability, without decrease after 5 cycles, compared with pure Ag3 PO4 nanoparticles. Positive synergy between Ag3 PO4 nanoparticles and BCN nanosheets, including the increase in the number of active adsorption sites, and the restriction of the formation of Ag due to the recombination of photogenerated electron-hole pairs in Ag3 PO4 nanoparticles, are mainly responsible for the enhanced properties of the prepared catalyst. This study shows that Ag3 PO4 /BCN composite photocatalyst would be promising for wastewater treatment, which would be of clearly environmental and public health relevance. Graphical abstract: Image 1 Highlights: Ag3 PO4 /BCN photocatalyst was synthesised via electrostatically driven self-assembly. Recombination of photogenerated electron-hole pairs in Ag3 PO4 could be inhibited. Ag3 PO4 /BCN dispalyed the enhanced photocatalytic activity compared with Ag3 PO4 .